SOCIO-PHILOSOPHICAL ASPECTS OF THE DYNAMICS OF ENTREPRENEURIAL CULTURE IN UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
The scientific article provides a scientific and philosophical analysis of the importance of national and universal values in improving entrepreneurial culture in foreign countries and foreign models of entrepreneurial culture development, opportunities for Uzbekistan to gain experience in improving entrepreneurial culture. The concept of “entrepreneurial culture” is included in a number of mobile, unstable categories. This concept characterizes professional culture and, in turn, manifests itself as a phenomenon more related to the socio-economic sphere. The starting point is the realization that entrepreneurship is a totality that includes industries that generate new professions, all the elements that make up the entrepreneurship system.